Amplifying Radiotherapy by Evoking Mitochondrial Oxidative Stress using a High-performance Aggregation-induced Emission Sonosensitizer - Li, Xing; Sun, Yingshu; Wang, Yilin; Zhou, Ye; Bao, Yixuan; Zhang, Zhuomiao; Liu, Shujing; Yang, Huini; Zhang, Ruoyao; Xia, Peng; Ji, Meiju; Hou, Peng; et al. (Current Medicinal Chemistry, 2025)
IntroductionDeveloping effective methods to enhance tumor radiosensitivity is crucial for improving the therapeutic efficacy of radiotherapy (RT). Due to its deep tissue penetration, excellent safety profile, and precise controllability, sonosensitizer-based sonodynamic therapy (SDT) has recently garnered significant attention as a promising combined approach with RT.MethodsHowever, the limited reactive oxygen species (ROS) generation ability in the aggregated state and the absence of specific organelle targeting in sonosensitizers hinder their potential to augment RT. This study introduces a fundamental principle guiding the design of high-performance sonosensitizers employed in the aggregated state. Building upon these principles, we develop a mitochondria-targeted sonosensitizer molecule (TCSVP) with aggregation-induced emission (AIE) characteristics by organic synthesis. Then, we demonstrate the abilities of TCSVP to target mitochondria and produce ROS under ultrasound in H460 cancer cells using confocal laser scanning microscopy (CLSM) and fluorescence microscopy. Subsequently, we examine the effectiveness of enhancing tumor radiosensitivity by utilizing TCSVP and ultrasound in both H460 cells and H460 and 4T1 tumor-bearing mice.ResultsThe results indicate that evoking non-lethal mitochondrial oxidative stress in tumors by TCSVP under ultrasound stimulation can significantly improve tumor radiosensitivity (p <0.05). Additionally, the in vivo safety profile of TCSVP is thoroughly confirmed by histopathological analysis.ConclusionThis work proposes strategies for designing efficient sonosensitizers and underscores that evoking non-lethal mitochondrial oxidative stress is an effective method to enhance tumor radiosensitivity.
Keywords: mitochondrial targeting